EXAMPLE OF METHODOLOGY FOR MEASURING HUMAN RESOURCES MOTIVATION AS A FACTOR FOR PREVENTING CORRUPT BEHAVIOR AMONG EMPLOYEES OF THE MINISTRY OF INTERNAL AFFAIRS - Todorova, Irena (Annals of Spiru Haret University. Economic Series, 2023)
The report presents the objective need to maintain a high level of motivation and effectiveness of training to achieve high-quality professional performance of official duties among the employees of the Ministry of Internal Affairs. The activity of the state administration should correspond to the high public expectations for professional competence, legality, integrity, correctness and responsibility. Therefore, the measurement of the motivation factor is a natural necessity, determining the managerial impact of the management team for the formation of specific behavior among employees, aimed at achieving a quality professional achievement in the performance of official duties and preventing corrupt behavior.